Sustainable Development in a Quilombola Community: analysis of the Restinga Community, Lapa, Paraná, Brazil - Garcia, Luciano; Bueno Wandscheer, Clarissa (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
The present study aims to analyze the global socio-ecological crisis, highlighting the complexity of interconnected challenges, such as energy scarcity, climate change, economic inequalities and environmental degradation. In addition, it explores the emergence of the Theory of Good Living as an alternative to harmonize humans, nature and community. The objective is to analyze the quilombola communities of Paraná (Brazil) and their relationship with the Theory of Good Living for sustainable development. The research follows a qualitative and exploratory approach, with a hypothetical-deductive design. Data collection involved interviews and questionnaires, and the analysis was based on the principles of the Theory of Good Living. The results highlight that quilombola communities value a holistic perspective, recognizing the interdependence between geography, culture, economic activities, and history. Collaboration with associations and cooperatives emerges as crucial for economic sustainability and well-being. The Theory of Good Living offers an alternative centered on culture, quality of life and harmony with nature. The study contributes by questioning the traditional approach to sustainable development and by exploring the application of the Theory of Good Living as an alternative perspective. In addition, the methodology adopted, combining interviews, questionnaires and analysis based on the principles of the theory, presents an innovative approach to examine the relationship between sustainable development and traditional cultures. The conclusions underscore the importance of sustainable practices, collective collaboration, and cultural appreciation in addressing current challenges. Quilombola communities are recognized as essential for the preservation of biodiversity and culture in Brazil. The study also emphasizes the need for a transformation in environmental management, promoting balanced coexistence between natural resources and cultural traditions.